Two vacuolar invertase inhibitors PpINHa and PpINH3 display opposite effects on fruit sugar accumulation in peach - Mollah, Md Dulal Ali; Zhang, Xian; Zhao, Li; Jiang, Xiaohan; Ogutu, Collins O.; Peng, Qian; Belal, Mohammad A. A.; Yang, Qiurui; Cai, Yaming; Nishawy, Elsayed; Cherono, Sylvia; Wang, Lu; et al. (Frontiers in Plant Science, 2022)
Soluble sugars are an important determinant of fruit taste, but their accumulation mechanisms remain elusive. In this study, we report two vacuolar invertase inhibitor genes involved in sugar accumulation in peach, PpINHa and PpINH3. Transient overexpression of PpINH3 in peach fruits resulted in an increase in sugar content, while the opposite trend was detected for PpINHa. Unexpectedly, PpINH3 and PpINHa both had no physical interaction with vacuolar invertase (VIN). Moreover, the PpVIN genes had no or extremely low expression in fruits at the ripening stage. These results suggested that the regulatory role of PpINHa and PpINH3 in sugar accumulation is unlikely due to their interaction with PpVINs. Additionally, overexpression of PpINHa and PpINH3 had an impact on transcription of genes related to fruit sugar metabolism and transport, which is likely responsible for their regulatory role in fruit sugar accumulation. Altogether, these results indicated an important role of PpINHs in fruit accumulation in peach. Our study provides new insights into molecular mechanisms underlying sugar accumulation, which could be useful for genetic improvement of fruit taste in breeding programs of peach and other fruit crops.